Mr. Darcy's diary - Grange, Amanda (Naperville, Illinois Sourcebooks, 2007)
The only place Darcy could share his innermost feelings...was in the private pages of his diary. Torn between his sense of duty to his family name and his growing passion for Elizabeth Bennet, all he can do is struggle not to fall in love. A skillful and graceful imagining of the hero's point of view in one of the most beloved and enduring love stories of all time.
Keywords: Darcy, Fitzwilliam(Fictitious character) -- Fiction; Bennet, Elizabeth(Fictitious character) -- Fiction; England -- Fiction; Domestic fiction; Diary fiction